Artificial intelligence driven human resource transformation: a systematic literature review on competencies roles and strategies - Anak Agung Gede Darma Jata; Riki Haryono (Jurnal Mantik, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly reshaped human resource management (HRM). However, existing studies remain fragmented, primarily focusing on operational efficiency while lacking an integrated understanding of how AI transforms HR competencies, job roles, and strategic development. This study aims to analyze AI-driven human resource transformation by identifying key changes in competencies, roles, and organizational strategies. A systematic literature review (SLR) approach was employed using the PRISMA framework, analyzing articles indexed in Scopus and Web of Science published between 2018 and 2024. The findings reveal three major transformations: (1) a shift from administrative to strategic HR roles driven by data analytics, (2) the emergence of hybrid competencies combining digital, analytical, and adaptive skills, and (3) the integration of AI into HR development strategies through continuous learning systems. This study contributes by proposing a conceptual framework of AI-based HR transformation, integrating technological, human, and organizational dimensions. Practically, the findings provide insights for organizations in designing adaptive and sustainable HR strategies in the digital era.